Operations Strategy and Technological Change - داود غسان قاسم (Journal of Economics and Administrative Sciences, 2007)
This research aims to deal with contemporary knowledge methodology to correlate between operations strategy and technological change or modernization in productive paths for industrial organizations depend on practical indicators for competitive priorities that is objectives of operations performance. The research is based on main hypothesis, concentrates on determination of technological change which is decided by the level of technology deterioration in current operations path compared with the competitors leaders-technology leaders. We apply these concepts on hypothetical case to two similar companies in their production nature and technological path. The outcomes showed proofs of indicators and elements of operations strategy in modernization and technological change.